2001
DOI: 10.1073/pnas.211287498
|View full text |Cite
|
Sign up to set email alerts
|

Corn pollen deposition on milkweeds in and near cornfields

Abstract: The density of corn pollen on leaves of milkweed plants inside and outside of cornfields was measured in several studies from different localities. The purpose was to obtain a representative picture of naturally occurring pollen densities to provide a perspective for laboratory and field studies of monarch larvae feeding on milkweed leaves with Bt corn pollen. Pollen density was highest (average 170.6 grains per cm 2 ) inside the cornfield and was progressively lower from the field edge outward, falling to 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
165
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 9 publications
5
165
2
3
Order By: Relevance
“…Crop byproducts from Bt corn contain this toxin (3,4), but until now the effects of Bt corn byproducts on stream organisms have not been examined. This is in sharp contrast to numerous studies examining potential effects on nontarget organisms in the terrestrial environment (4)(5)(6)(7)(8).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Crop byproducts from Bt corn contain this toxin (3,4), but until now the effects of Bt corn byproducts on stream organisms have not been examined. This is in sharp contrast to numerous studies examining potential effects on nontarget organisms in the terrestrial environment (4)(5)(6)(7)(8).…”
mentioning
confidence: 65%
“…During pollen shed, wind can transport corn pollen from 40 to 60 m away from source fields (10), and rain can dislodge and transport pollen away from crops (6). After harvest, crop byproducts remain on fields and may be transported to adjacent streams via wind and water.…”
mentioning
confidence: 99%
“…This study led to considerable debate over the environmental impact and relevance for the potential risks from Bt maize. Follow-up studies to investigate the impact of widespread plantings Bt-maize on the Monarch butterfly essentially concluded that the impact of Bt-maize pollen from current commercial hybrids on Monarch butterfly populations is negligible Oberhauser et al, 2001;Pleasants et al, 2001;Sears et al, 2001;Stanley-Horn et al, 2001;Zangerl et al, 2001). This is based on the low expression of Bt toxin genes in pollen for most maize hybrids, lack of acute toxicity at expected field rates, limited overlap of pollen shed and larval activity, and the limited overlap in distribution of Bt-maize and milkweed.…”
Section: Will Gm Crops Have Secondary Ecological Impacts?mentioning
confidence: 99%
“…La toxine Cry1Ac purifiée d'une lignée de coton transgénique, par exemple, s'est avérée bénigne en laboratoire pour une dizaine d'insectes herbivores ou prédateurs non ciblés, mais toxique à fortes doses contre plusieurs insectes lépidoptères apparentés à l'insecte visé (Sims 1995 Zangerl et al 2001). Si des facteurs variés comme le faible taux d'expression de la toxine Cry1Ab dans les lignées de maïs Bt actuellement disponibles, la faible quantité de pollen déposée sur les feuilles d'asclépiade dans les champs ou la préférence des adultes pour des feuilles d'asclépiade sans pollen au moment de la ponte Pleasants et al 2001;Tschenn et al 2001) suggèrent des impacts négligeables de ces hybrides sur le papillon en comparaison aux effets négatifs des mesures phytosanitaires adoptées pour la répression des mauvaises herbes et des insectes en systèmes conventionnels (Gatehouse et al 2002;Sears et al 2001;Shelton et Sears 2001;Wolt et al 2003 Les différentes études menées en laboratoire et en champ concernant l'impact des cultures transgéniques Bt sur la croissance, le développement ou la survie des arthropodes herbivores non ciblés ont conduit à des conclusions variables en fonction : (i) du degré de parenté entre l'insecte cible et l'organisme non ciblé; (ii) de la nature de l'interaction entre l'organisme étudié et la plante modifiée; et (iii) de la lignée végétale utilisée pour les tests (Tableau 1). En lien avec l'action des toxines du Bt contre certains groupes d'insectes, des effets négatifs ont été notés dans les cas où l'espèce considérée était apparentée à l'insecte visé par la toxine exprimée.…”
Section: Impacts Directs Sur Les Arthropodes Herbivores Et Pollinisatunclassified